2016
DOI: 10.1073/pnas.1509333113
|View full text |Cite
|
Sign up to set email alerts
|

Stochastic modeling reveals an evolutionary mechanism underlying elevated rates of childhood leukemia

Abstract: Young children have higher rates of leukemia than young adults. This fact represents a fundamental conundrum, because hematopoietic cells in young children should have fewer mutations (including oncogenic ones) than such cells in adults. Here, we present the results of stochastic modeling of hematopoietic stem cell (HSC) clonal dynamics, which demonstrated that early HSC pools were permissive to clonal evolution driven by drift. We show that drift-driven clonal expansions cooperate with faster HSC cycling in y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
25
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 47 publications
5
25
0
Order By: Relevance
“…Estimates for the size of this pool vary widely. [43][44][45] The model was also sensitive to the value of p, Hazard ratio (95% Cl)…”
Section: Modeling Clonal Hematopoiesis Caused By Neutral Driftmentioning
confidence: 99%
“…Estimates for the size of this pool vary widely. [43][44][45] The model was also sensitive to the value of p, Hazard ratio (95% Cl)…”
Section: Modeling Clonal Hematopoiesis Caused By Neutral Driftmentioning
confidence: 99%
“…To address this, we suggest that selection for oncogenic clones is highly dependent on tissue context, which changes with age, and necessarily implies that clonal evolution is differentially regulated throughout life. As the probability of sequential mutation accumulation in one cell depends both on cell division rates and the number of dividing cells, early in life when cells cycle rapidly, the lower observed risk of cancer should require that those cells that acquire mutations do not expand into multi-cell clones (which would increase the target size for the next oncogenic mutation) [10]. Late in life, the slow cell division program needs to be compensated by more profound clonal expansions of pre-malignant cells to provide for the elevated risk of cancers that require multiple mutations.…”
Section: The Armitage-doll Multi-stage Paradigm Of Carcinogenesis In mentioning
confidence: 99%
“…It could already be shown that aging of the HSCs niche and environment plays an important role in selecting and expanding normal and pre-leukemic HSC and HPC clones upon aging (Vas, Senger, et al 2012; Vas, Wandhoff, et al 2012). Thus the concept of adaptive landscapes has been recently developed (Rozhok, Salstrom, and DeGregori 2016). In this concept, the niche environment of HSCs changes upon aging, influencing the functionality of HSCs.…”
Section: Perspectivementioning
confidence: 99%